HISTOPHYSIOLOGY OF SUBMANDIBULAR SALIVARY GLANDS END PIECES IN RATS WITH CHRONIC ETHANOL INTOXICATION - Shevchenko, K.V.; Garets, V.I.; Fedonyuk, L.Ya.; Volkov, K.S.; Nesteruk, C.O. (World of Medicine and Biology, 2018)
The paper presents the morphometric study of the submandibular salivary gland parenchyma in chronic intoxication with ethanol. It has been established, that chronic ethanol intoxication affects the morphofunctional state of the submandibular gland lobules’ end pieces in rats, which is confirmed by the lumen diameter reduction and the epithelial cells height growth up to 15.44 ± 0.41 µm at the early stages of observation. Reduction in the external diameter and the lumen diameter with the reduced epithelial cells height were observed on the thirtieth day of the experiment. This is due to dystrophic changes in the cells of the of the submandibular glands end pieces in rats at the later stages of the experiment, and is confirmed by reduction in their size, the number of secretory granules and the increased optical density of cells.